ChemInform Abstract: Antibacterial and Antifungal Vaccines Based on Synthetic Oligosaccharides. Issue 34 (26th August 2014) - Balbin, Yury Valdes; Rodriguez, Maria C.; Bencomo, Vicente Verez
Abstract Review: 194 refs.